2022
DOI: 10.3168/jds.2021-21678
|View full text |Cite
|
Sign up to set email alerts
|

Combined biotin, folic acid, and vitamin B12 supplementation given during the transition period to dairy cows: Part II. Effects on energy balance and fatty acid composition of colostrum and milk

Abstract: Biotin (B 8 ), folate (B 9 ), and vitamin B 12 (B 12 ) are involved in several metabolic reactions related to energy metabolism. We hypothesized that a low supply of one of these vitamins during the transition period would impair metabolic status. This study was undertaken to assess the interaction between B 8 supplement and a supplementation of B 9 and B 12 regarding body weight (BW) change, dry matter intake, energy balance, and fatty acid (FA) compositions of colostrum and milk fat from d −21 to 21 relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Even though B 8 −/B 9 B 12 + cows produced 13.5% more milk than B 8 −/B 9 B 12 − cows, they only tended to have greater plasma NEFA concentration than control cows. In the companion pa-per, we showed that these cows lost more BW (5.3% of BW for B 8 −/B 9 B 12 + and 2.1% of BW for B 8 −/B 9 B 12 −) within the first 21 DIM (Duplessis et al, 2022). In opposition to the latter results, B 8 +/B 9 B 12 − cows had greater plasma NEFA concentration and BW loss than B 8 −/B 9 B 12 − cows, combined with a nonsignificant milk yield increase and a trend for a decreased DMI.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Even though B 8 −/B 9 B 12 + cows produced 13.5% more milk than B 8 −/B 9 B 12 − cows, they only tended to have greater plasma NEFA concentration than control cows. In the companion pa-per, we showed that these cows lost more BW (5.3% of BW for B 8 −/B 9 B 12 + and 2.1% of BW for B 8 −/B 9 B 12 −) within the first 21 DIM (Duplessis et al, 2022). In opposition to the latter results, B 8 +/B 9 B 12 − cows had greater plasma NEFA concentration and BW loss than B 8 −/B 9 B 12 − cows, combined with a nonsignificant milk yield increase and a trend for a decreased DMI.…”
Section: Discussionmentioning
confidence: 80%
“…Within the first 21 DIM, milk and TS yields and ECM of B 8 −/B 9 B 12 + cows were the highest among treat- (Duplessis et al, 2022). Similarly, Girard and Desrochers (2010) concluded that a dietary supplement of B 8 altered ruminal fermentation, which might suggest that the DMI decline in B 8 + cows could be linked to the possible altered ruminal function with this supplementation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Required for one-carbon metabolism are choline, folic acid and vitamin B12. Recently, Duplessis et al [6] [7] found that weekly injections of folic acid and vitamin B12 beginning prepartum resulted in increased energy corrected milk and numerically lower blood beta hydroxy butyric acid (BHBA) in early lactation. The inclusion of biotin in the diet, on the other hand, did not improve milk production or alter BHBA in these studies.…”
Section: Introductionmentioning
confidence: 99%